Oil and Gas Conference. Day 3. Tape 06. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Speech by Dr. Ian MacKay continued (economics of oil development); Questions (cost and benefits of capital investment); Close.